The Output Decline in Asian Crisis Countries : Investment Aspects - Greene, Joshua (IMF Working Papers; Working Paper ;, 2002)
This paper examines whether capital outflows may have contributed to output declines during the Asian Crisis by reducing the financing available for domestic investment. Panel data regressions suggest a positive, short-term relationship between net capital inflows and investment during the period before 1997 in five Asian countries once real net capital flows are netted out from real flows of private bank credit. In addition, net real private inflows and real private investment appear to have been cointegrated in at least three of these countries, suggesting a long-term relationship as well.